Job satisfaction and compensating wage differentials: Evidence from Russia. (23rd September 2017) - Bartolucci, Francesco; Bruno, Giovanni S F; Demidova, Olga; Signorelli, Marcello
Abstract: This article is focused on the analysis of the determinants of job satisfaction of Russian workers through the estimation of ordered logit models with individual fixed effects on a panel data set extracted from the Russian Longitudinal Monitoring Survey. The real wage results positively associated with job satisfaction on all samples considered, after controlling for several time-varying controls aimed at picking up time-varying human capital, preferences, and non-instantaneous equilibrium adjustments. As long as the included controls capture all the heterogeneous trends in individual wages, we may interpret this result as a possible failure of the theory of compensating wage differentials in the Russian labour market. (JEL codes: J28, J81)